2018
DOI: 10.1021/acs.energyfuels.8b02055
|View full text |Cite
|
Sign up to set email alerts
|

Biofuel Surrogate Oxidation: Insoluble Deposits Formation Studied by Small-Angle X-ray Scattering and Small Angle Neutron Scattering

Abstract: The stability of biofuels toward oxidation is currently one of the major challenges for its widespread use. In fact, insoluble deposits issued from biofuels degradation can cause several types of damages with the blockage of injectors, filters, and lines in contact with the fuel, seriously compromising the operation of the engines and aircraft turbines. The aim of this work was to characterize a surrogate biofuel (90% n-dodecane and 10% methyl oleate) under different oxidation conditions (110, 130, and 150 °C,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 49 publications
0
2
0
Order By: Relevance
“…Supramolecular characterization, dynamic kinetics and mechanistic studies coupled with more accurate X-ray measurements can be used to obtain more information on the formation of particles followed by their deposition in the engine system. A biofuel surrogate was tested by Alves-Fortunato et al 140 in oxidation tests conducted in a Parr reactor under different conditions. Small-angle X-ray scattering and small-angle neutron scattering were used to follow the nucleation and growth steps of the insoluble deposit precursors.…”
Section: Further Chemical Analytical Techniquesmentioning
confidence: 99%
“…Supramolecular characterization, dynamic kinetics and mechanistic studies coupled with more accurate X-ray measurements can be used to obtain more information on the formation of particles followed by their deposition in the engine system. A biofuel surrogate was tested by Alves-Fortunato et al 140 in oxidation tests conducted in a Parr reactor under different conditions. Small-angle X-ray scattering and small-angle neutron scattering were used to follow the nucleation and growth steps of the insoluble deposit precursors.…”
Section: Further Chemical Analytical Techniquesmentioning
confidence: 99%
“…According to Fang et McCornick, [10] autoxidation products could be kept in suspension into the liquid phase fuel depending on their polarity and/or molecular weight as well as the interaction with the solvent. Our last work [11] on oxidation process of biofuel surrogate (methyl oleate/n-dodecane) has shown that during oxidation small aggregates are formed, fuel color changes and phase separation occurs when the number of clusters in the liquid phase is higher than 10 and with a molecular weight larger than 3500 g/mol, the aggregates sizes increases linearly with the number of particles and, at the same time, oxygenate products epoxides and ketones can be identified, they could certainly increase the polarity of the sample.…”
Section: Introductionmentioning
confidence: 99%